(untitled) (Research, Society and Development, 2021)
This paper aims to present the difficulties encountered in complying with Regulatory Standard No 31 - Occupational Health and Safety in Agriculture, Livestock, Forestry, Forestry and Aquaculture, in rural areas. The research was carried out through consultations in several scientific articles and was justified by the need to make field workers aware of the risks to which they are exposed, in the exercise of their activity. Through several studies that supported this work, it was possible to verify that the use of NR 31 is flawed, even with the scope and detail provided in its text. In the study it was found that, the rural work environment is worrying, due to the numerous risks that are present in the exercise of their activities and the disregard for non-compliance with NR-31. It is essential that government authorities, in addition to inspecting the faithful compliance with the standard, must carry out a work of awareness of workers and employers, aiming to provide an improvement in working conditions in the rural environment. The prioritization that should be given to awareness, education, training, and adequacy of working conditions becomes relevant, as a measure to prevent accidents and diseases in the agricultural sector.